Determinants affecting purchase intention of halal products: an article review - Fitry Oktavia Fatmi; Anis Najiha Ahmad; Betania Kartika (Journal of Halal Product and Research)
This study's main objectives are to analyze the literature related to the factors influencing halal products' purchase intention and identify the literature gap for future study recommendations. The researchers evaluate the numerous assessed studies conducted in different countries. Halal products' major determinants in purchase intention are attitude, subjective norm, perceived behaviour control, religiosity, halal awareness, and halal certification. The researchers found few studies that examined factors such as price, exposure, place, halal supply chain, and advertising in their studies. Common theories used in previous literature are the Theory of Planned Behavior (TPB). One of the gaps for further research on halal products' purchase intention is the lack of research in the halal pharmaceutical, halal fashion, halal tourism, halal supply chain, and halal finance fields. In the future, the researcher may apply other theories that can be used to study purchase intention, such as theory consumption value or theory diffusion of innovation.